The Journalist between the Profession and the Newspaper's Interests: Values and Routines in the Production of Folha De S. Paulo’s Editorials - Mont'Alverne, Camila; Athanásio, Ester; Marques, Francisco Paulo Jamil (Brazilian journalism research, 2018)
Notwithstanding journalistic editorials may evidence conflicts and negotiations involving public and private interests, their production process is little investigated in Brazil. The article examines the values and routines typical to the work of Folha de S. Paulo’s editorialists to find out how they construct newspaper’s positions. By applying Content Analysis to three in-depth interviews, we propose four thematic axes regarding the features of journalistic editorials: Political and marketing roles; their target audience; production routines; and editorial values of the newspaper. The results indicate that editorialists exercise limited autonomy, striving to fit the positions historically defended by the publication. Such a condition is seen as natural by the interviewees, with no record of tensions between their individual opinions and newspaper’s positions. Embora o editorial possa tornar evidentes conflitos e negociações envolvendo interesses públicos e privados na atividade jornalística, seu processo de produção é pouco investigado no Brasil. O objetivo do artigo é examinar, a partir do estudo de valores e rotinas inerentes à atuação dos editorialistas, os modos pelos quais os posicionamentos da Folha de S. Paulo (FSP) são construídos. A Análise de Conteúdo de três entrevistas em profundidade realizadas com profissionais da FSP permitiu sistematizar quatro eixos temáticos acerca dos editoriais: função política; público-alvo; rotinas produtivas; e valores da empresa. Os resultados indicam que os editorialistas exercem autonomia limitada, esforçando-se para se enquadrar no histórico de posições da empresa. Tal condição é vista com naturalidade pelos entrevistados, sem registro de tensões entre opiniões individuais e posicionamentos institucionais. Aunque el editorial sea capaz de evidenciar conflictos y negociaciones entre el interés público y privado en la práctica periodística, su proceso productivo es poco examinado en Brasil. El objetivo del artículo es analizar, a través del estudio de valores y rutinas inherentes a la actuación de los editorialistas, como los posicionamientos de Folha de S. Paulo son diseñados. El Análisis de Contenido de tres entrevistas en profundidad realizadas con profesionales de FSP ha sido organizada en cuatro ejes temáticos acerca de los editoriales: función política; público objetivo; rutinas de producción; y valores de la empresa. Los resultados indican que los editorialistas tienen una autonomía limitada y que se adaptan al historial de posicionamientos de la compañía. Esta adecuación es percibida con naturalidad, sin registro de tensiones entre opiniones individuales y posicionamientos institucionales.